Efficacy of Danshen Class Injection in the Treatment of Acute Cerebral Infarction: A Bayesian Network Meta-Analysis of Randomized Controlled Trials. (3rd February 2019) - Liu, Shi; Wang, Kaihuan; Duan, Xiaojiao; Wu, Jiarui; Zhang, Dan; Liu, Xinkui; Zhao, Yi
Abstract : Introduction. As a common chronic disease with high morbidity and recurrent rate, acute cerebral infarction (ACI) affects the life quality of patients and gives them heavy psychological burden. And Danshen class injections (DSCIs) are commonly adopted in treating ACI. So, this network meta-analysis (NMA) was designed to assess the clinical efficacy of eight kinds of DSCIs. Methods. A systematic literature search was performed in PubMed, the Cochrane Library, Embase, the China National Knowledge Infrastructure Database, the China Biomedical Literature Service System, the Chinese Scientific Journals Full-text Database, and Wanfang database from their inception to16 t h Dec. 2017 aiming to collect related randomized controlled trials (RCTs). And then data were analyzed through Stata and WinBUGS software based on the Bayesian statistical model. The results were reported as odds ratio (OR) and mean difference (MD) with 95% credible intervals (CIs). The consistency test between direct and indirect comparisons was also evaluated and inconsistency factor was presented to manifest the heterogeneity among them. Meanwhile, the surface under the cumulative ranking probabilities (SUCRA) was utilized to rank the treatments in different outcomes. Results . Finally, 157 RCTs with 15570 patients were included. A total of eight types DSCIs were identified. Based on the results, Sodium Tanshinone IIA Sulfonate injection (STS) plus western medicine (WM) had better effect on the clinical effectiveness rate, neurological impairment, and activities of daily living function than others. Meanwhile, Danhong injection (DS) and Danshen Salvianolic Acids injection (DSSA) had excellent performance in perfecting hemorheological indexes. Conclusions. In conclusion, STS plus WM may be the optimum treatment for ACI. The following therapies were DS plus WM and DSSA plus WM. Nevertheless, in terms of the limitations of the study, more large samples, multicenter, and double-blind RCTs are still needed for validating our findings.